2018
DOI: 10.1111/fare.12315
|View full text |Cite
|
Sign up to set email alerts
|

The Decision‐Making Process for Disclosing Suicidal Ideation and Behavior to Family and Friends

Abstract: Objective This study was designed to explore the decision‐making processes for disclosing suicidal ideation and behavior. Background Suicide attempt survivors are an invaluable resource that can provide essential information about suicidal behavior and related communication to family and friends. Because of the stigma associated with suicide and seeking help, many individuals choose to conceal their suicidal ideation or behavior or to disclose only to a few family and friends. Method Semistructured, audio‐only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
35
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 22 publications
7
35
1
Order By: Relevance
“…If an attempter perceives their environment to be invalidating, our results suggest this may lead to an increased urge to conceal warning signs and even attempt suicide to avoid feeling worse. This is consistent with previous studies of suicide attempt survivors that have found fears about receiving unsupportive responses, being rejected, and being stigmatized as primary reasons preventing disclosure (e.g., Frey et al, 2018;Sheehan et al, 2019). Some individuals might also interpret their environment to be invalidating after the exhibition of warning signs is not taken seriously.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…If an attempter perceives their environment to be invalidating, our results suggest this may lead to an increased urge to conceal warning signs and even attempt suicide to avoid feeling worse. This is consistent with previous studies of suicide attempt survivors that have found fears about receiving unsupportive responses, being rejected, and being stigmatized as primary reasons preventing disclosure (e.g., Frey et al, 2018;Sheehan et al, 2019). Some individuals might also interpret their environment to be invalidating after the exhibition of warning signs is not taken seriously.…”
Section: Discussionsupporting
confidence: 91%
“…This exploratory qualitative study sought to gain a better understanding of the complexity of predicting suicide by speaking directly to individuals with lived experience. Consistent with previous literature highlighting the cost-benefit determination suicidal individuals consider before disclosing their ideation or intent (e.g., Frey, Fulginiti, Lezine, & Cerel, 2018;Sheehan et al, 2019), our results suggest there is a notable disconnect between attempters and their environment. The superordinate theme of a disconnect between attempters and their environment was first indicated through a sense of ambivalence regarding whether or not participants wanted help prior to their attempts, which is consistent with prior research (Bruffaerts et al, 2011;Czyz et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Results indicated a majority (63%) of undergraduate students disclose their suicide attempt to at least one social network member. Additionally, the majority of those who disclose (81%) reported disclosure to two or fewer DSA targets, supporting previous research indicating survivors of suicide attempts are very selective in choosing DSA targets (Frey et al, ). Individuals chosen as DSA targets by the present sample were comparable to those reported by a sample of middle‐aged adults (Frey et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…To our knowledge, prevalence of DSA, the DSA target’s (person selected for disclosure) relationship to the discloser (e.g., friend, significant other), and levels of suicide risk associated with disclosure have not previously been studied in a sample of undergraduate college students. Although Frey, Fulginiti, Lezene, and Cerel () reported common relationships with disclosure targets, these data have not been reported for a sample of undergraduate college students. Similarly, Fulginiti, Pahwa, Frey, Rice, and Brekke () reported the prevalence of disclosure and type of relationship to disclosure target for individuals who had disclosed suicide ideation, but no such work has been conducted for individuals who have disclosed suicide attempts.…”
mentioning
confidence: 66%
See 1 more Smart Citation